Effect of tunnel on the resistance of high-speed planing craft - Subramanian, V Anantha; Subramanyam, PVV (Journal of Naval Architecture and Marine Engineering, 2009)
Tunnels are provided in ship hulls to accommodate propellers under reduced draught conditions, thereby avoiding reduction of propeller diameter and consequent loss of efficiency. In this work the hydrodynamic effect of propeller tunnels in high speed craft, by way of modified resistance and pressure distribution, are studied both numerically using CFD, and experimentally using geometrically scaled models. The experimental study has been conducted on the model of a single hard chine hull form designed for specific length to displacement ratio. The parametric study considers two other draught conditions. In order to bring out pressure influences, CFD based simulations have been carried out. It is noted that the pressure distributions are altered around the tunnel region and, for an investigated case of tunnel area ratio, there is consistent reduction of resistance for all the three draught conditions tested. The study also compares the merits of the modified Froude extrapolation method, after correction for flow velocity due to pressure development in the hull zone, with the classical Savitsky's method for planing hulls. The qualitative aspects with respect to pressure distribution are brought out in the CFD based studies and the pressure predictions do show consistency with obtained experimental data. Keywords: High speed planing craft, Tunnels, Resistance, Extrapolation methods, Pressure distribution, CFD Studies. doi: 10.3329/jname.v2i1.2025 Journal of Naval Architecture and Marine Engineering 2(1)(2005) 1-14